2020
DOI: 10.1530/ey.17.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Preconception diabetes mellitus and adverse pregnancy outcomes in over 6.4 million women: A population-based cohort study in China

Abstract: Background Diabetes mellitus (DM) increases the risk of adverse maternal and neonatal outcomes, and optimization of glycemic control during pregnancy can help mitigate risks associated with diabetes. However, studies seldom focus precisely on maternal blood glucose level prior to pregnancy. We aimed to evaluate the associations between preconception blood fasting plasma glucose (FPG) level and subsequent pregnancy outcomes. Methods and findings We conducted a population-based retrospective cohort study among 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
334
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(355 citation statements)
references
References 18 publications
14
334
3
4
Order By: Relevance
“…These studies confirmed an antagonism relationship between BR and ABA and provided a mechanism for balancing plant growth and drought survival (Nolan et al, 2017a;Nolan et al, 2019;Kono and Yin, 2020). In addition to drought, BZR1 and BES1 are also involved in plant responses to freezing (Li et al, 2017), heat (Yin et al, 2018;Albertos et al, 2022;Chen et al, 2022) and salinity stress. In the case of salt stress, BIN2 was found to act as a molecular switch to help plant recovery after non-lethal salt stress in Arabidopsis.…”
Section: Introductionsupporting
confidence: 54%
“…These studies confirmed an antagonism relationship between BR and ABA and provided a mechanism for balancing plant growth and drought survival (Nolan et al, 2017a;Nolan et al, 2019;Kono and Yin, 2020). In addition to drought, BZR1 and BES1 are also involved in plant responses to freezing (Li et al, 2017), heat (Yin et al, 2018;Albertos et al, 2022;Chen et al, 2022) and salinity stress. In the case of salt stress, BIN2 was found to act as a molecular switch to help plant recovery after non-lethal salt stress in Arabidopsis.…”
Section: Introductionsupporting
confidence: 54%
“…At 95 % RH, the conductivity increases to 4.15×10 −6 S cm −1 . It also proves the critical role of H 2 O in the proton conduction process [30,31] . Moreover, the fluidity of H 2 O increases at high temperature and enhance the proton conduction performance.…”
Section: Resultsmentioning
confidence: 55%
“…Considering that PpS6PDH is a reversible enzyme, its role in fruit ripening requires further investigation. In apples, activation of a pyrophosphate-dependent phosphofructokinase gene can promote soluble sugar accumulation (Yu et al, 2022). In sweet pear cultivars evaluated in the present study, the gene encoding 6phosphofructokinase 7 was upregulated.…”
Section: Discussionmentioning
confidence: 50%